Teacher’s Communication Strategies in Teaching English to Kids - Maisarah, Maisarah (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2024)
In the teaching process, appropriate communication strategies are very important in teaching children because they significantly impact their learning effectiveness. Using communication strategies that align with children's understanding level and interests, educators can facilitate good comprehension, enhance information retention, encourage active engagement, strengthen social skills, and increase children's motivation and interest in learning. This research analyzes teachers' communication strategies in this video based on Bandura's theory: Attention, Retention, Reproduction, and Motivation. This qualitative research analyzes data obtained from video on YouTube titled How to teach Kids | from a Prague kindergarten, part 1 | English for Children." The research findings show that teacher successfully applies various effective communication strategies in teaching language to children. The teacher successfully aroused the children's attention by using engaging elements, such as bright colors, relevant pictures, enjoyable, energetic voices, and positive interaction between the teacher and the children.